The Effect of UVB Exposure at Collagen Density and Dermal Thickness of Wistar Rats: A Pilot Study - Siti Efrida Fiqnasyani; Endra Yustin Elistasari; Nurrachmat Mulianto (HM Publisher, 2023)
Background: Skin aging has been characterized by decreasing skin regeneration and loss of structure and function. The most significant cause of extrinsic skin aging is exposure to ultraviolet (UV) radiation (80%). UVB radiation causes DNA damage which leads to dermal thickness reduction. This study aimed to compare the features of collagen density and dermal thickness of rats before and after UVB exposure. Methods: This experimental study was conducted at the experimental animal laboratory of Universitas Setia Budi, Surakarta, from May to June 2022. The male Wistar rats were epilated and given UVB exposure, and a back skin biopsy was performed before and after the total dose of UVB exposure. The UVB exposure dose was 50 mJ/cm2 in the first week, 60 mJ/cm2 in the second week, and 70 mJ/cm2 in the third and fourth weeks. The UVB tool used was the Kernel® UV Phototherapy KN-4003BL UVB lamp. Results: The collagen densities before vs. after total dose UVB exposure are 61.9% vs. 50.3% for 4x magnification and 63.8% vs. 49.6% for 10x magnification. The dermal thickness also reduced from 1422.07 ± 1165.96 µm before the total dose of UVB exposure to 1049.52 ± 1018.97 µm after the total dose of UVB exposure. Conclusion: UVB exposure can induce decreased collagen density and dermal thickness in Wistar skin rats, similar to photoaging.